Improving Thermal Performance of the Wall Panels Using Slotted Steel Stud Framing. (2016) - Lupan, Lidia Maria; Manea, Daniela Lucia; Moga, Ligia Mihaela
Abstract: Nowadays application of cold formed steel framing as structural elements had experienced a great development, and currently this system is met in almost all aspects of modern life [1] . There are many more advantages than might appear at first glance. Their development is highlighting the need to build as easy and as safe in a short time, all at top quality and affordable price. This paper proposes a study of hygrothermal behavior of panel sections made of slotted light steel framing, in order to improve thermal performance. Hygrothermal characteristics of the sections were determined using tridimensional computer programs UNORM and ABAQUS 6.11. Starting from a basic pattern, there have been developed twelve cases of perforation. The new profiles were obtained through variation of certain parameters defining the slotted segments, seven versions that had rectangular shape and five versions where the geometrical shape of the slots has been other than the rectangular one (oval, diamond, etc.).